Analisis Efisiensi Performa Daya Mampu Mesin SWD 6TM410 - Destio, Abednego; Hartono, Rudi; Umron, Amat (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
The SWD 6TM410 diesel engine is a engine located in the Kayu Merah PLTD which has been operating for 37 years since 1982 with an installed power of 3380 kW. Currently, the SWD 6 TM410 engine can only operate with the operating power of the 2200 kW engine so that there has been a decrease in performance on the operational power that is quite significant from the installed force. The data analysis began with a recapitulation of operating journals, a review of machine overhaul reports, an analysis of factors affecting power loss and a calculation analysis of power loss factors for the operation of the SWD 6TM410 engine. The last breakdown was in 2016 due to a malfunction of the lube oil pump. The pressure and temperature of the lubricant are the limits to be taken into account when operating the SWD 6TM410 engine. The temperature and pressure values of the Lubricant have the highest presentation with the value of the 8.3% lubricating temperature and 7.2% lubrication pressure against a decrease in the power capable of operating SWD6TM410. There was a change of size on the crankshaft resulting in measurement values on crankpin 3 and 4 deflections passing the tolerance limit. It is necessary to make a material request for a new Lube Oil Cooler to replace the old Lube oil cooler so that the pressure and temperature of the lubricant on the engine can be optimal. Operating the SWD 6TM410 engine does not exceed the operational power limit so it does not result in fatal interference with the engine and makes the operating power of the SWD 6 TM410 machine increasingly decreasing.